2021
DOI: 10.1002/jssc.202100604
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of caffeine and its metabolites in rat plasma by UHPLC‐MS/MS

Abstract: Caffeine is a widely consumed psychostimulant with several mechanisms of action and various positive and negative effects on organisms. Caffeine undergoes extensive hepatic metabolism to form main metabolites such as theobromine, theophylline, paraxanthine, and 1,3,7-trimethyluric acid. However, interspecies diversities have been observed in caffeine metabolism. In the present study, we developed a sensitive and straightforward ultra-high-performance liquid chromatography-tandem mass spectrometry method to qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The simultaneous analysis of caffeine and its metabolites has been recommended (Mendes et al, 2019). It has been reported that caffeine and its metabolites can successfully be analyzed together in some studies, but the close chromatographic retention times for theophylline and paraxanthine that generate similar product and precursor ions can be challenging (Chen et al, 2017; Kertys et al, 2021). In this study, a derivatization method was used to separate paraxanthine and theophylline to accurately analyze these two compounds in samples.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The simultaneous analysis of caffeine and its metabolites has been recommended (Mendes et al, 2019). It has been reported that caffeine and its metabolites can successfully be analyzed together in some studies, but the close chromatographic retention times for theophylline and paraxanthine that generate similar product and precursor ions can be challenging (Chen et al, 2017; Kertys et al, 2021). In this study, a derivatization method was used to separate paraxanthine and theophylline to accurately analyze these two compounds in samples.…”
Section: Discussionmentioning
confidence: 99%
“…By using an automated solid‐phase extraction device, this analysis can be done easily. The common features of the cartridges used in the extraction were that they are effective over wide pH ranges, they allow the simultaneous extraction of substances with different properties and have been used caffeine analyses before (Kertys et al, 2021). It is possible to use Oasis MCX cartridges, but the absorbance value is lower than that for the other cartridges.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, several disadvantages should be recognized, such as calibration to the particular drug, the imprecise results at low plasma levels, and none of the methods being specific enough for quantifying all DOACs in a single run [10]. LC-MS/MS presents a golden standard and powerful technique for multiple drug analysis [11][12][13], including DOACs monitoring in preclinical drug development [14,15]. Due to the high degree of specificity, sensitivity, and selectivity over the coagulation-based assays, the use of LC-MS/MS in clinical laboratories has significantly increased in past years for DOAC monitoring [16].…”
Section: Introductionmentioning
confidence: 99%